2020
DOI: 10.1007/s00253-020-10976-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bile acids on the growth and global gene expression profiles in Akkermansia muciniphila

Abstract: Akkermansia muciniphila is a prominent member of the gut microbiota and the organism gets exposed to bile acids within this niche. Several gut bacteria have bile response genes to metabolize bile acids or an ability to change their membrane structure to prevent membrane damage from bile acids. To understand the response to bile acids and how A. muciniphila can persist in the gut, we studied the effect of bile acids and individual bile salts on growth. In addition, the change in gene expression under ox-bile co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 60 publications
5
28
0
Order By: Relevance
“…As described above in this review, UDCA treatment can increase the abundance of A. muciniphila in mice (Van den Bossche et al 2017). Our group showed that DCA increased the growth of A. muciniphila in vitro and its bile acid-resistant metabolism (Hagi et al 2020). These studies indicate that the change in bile acids, especially UDCA, by the treatment of camu camu could increase the abundance of A. muciniphila, and the interaction between secondary bile acids and A. muciniphila might affect the host bile acid metabolism.…”
Section: Lactobacillusmentioning
confidence: 60%
See 2 more Smart Citations
“…As described above in this review, UDCA treatment can increase the abundance of A. muciniphila in mice (Van den Bossche et al 2017). Our group showed that DCA increased the growth of A. muciniphila in vitro and its bile acid-resistant metabolism (Hagi et al 2020). These studies indicate that the change in bile acids, especially UDCA, by the treatment of camu camu could increase the abundance of A. muciniphila, and the interaction between secondary bile acids and A. muciniphila might affect the host bile acid metabolism.…”
Section: Lactobacillusmentioning
confidence: 60%
“…Bile metabolism is strongly associated with gut microbiota because primary bile acids secreted by the host are converted to secondary bile acids by gut bacteria-harbouring bile modification enzymes associated with bile hydroxylation and deconjugation (Wahlström et al 2016). The growth of A. muciniphila is increased by a secondary bile acid (deoxycholic acid (DCA)) (Hagi et al 2020). DCA also increases the expression of MUC2 in human colon carcinoma cells (Song et al 2005).…”
Section: Human Oligosaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found a very interesting association between Akkermansia muciniphila and the secondary bile acid DCA. It has been reported that DCA increases the growth of Akkermansia muciniphila and helps in its survival in the gut [ 70 ]. In our experiments, DCA in Tempol treated animals was found to be substantially increased.…”
Section: Discussionmentioning
confidence: 99%
“…7α/β-dehydroxylation can also serve as an electronaccepting reaction for these bacteria, producing an NADPH molecule (101,173). Both DCA and LCA act as chemical signals for certain bacteria, leading to the upregulation of genes involved in colonization and growth, as well as triggering biofilm formation and leading to conformational changes to promote gut colonization and persistence (258)(259)(260)(261)(262)(263)(264). While 7α/β-dehydroxylation may be beneficial for some bacterial species, the minimum inhibitory concentration range for LCA and DCA is much lower than for conjugated and unconjugated primary BAs, likely due to the increased hydrophobicity, allowing for a more rapid transit of the secondary BA into the cell and the induction of similar stressors to bacteria (147,150,173,265).…”
Section: Bile Modification Impacts On the Microbiotamentioning
confidence: 99%